Kinetics and Thermodynamics of Oxidation of Some para-Substituted 4-Oxo-4-phenyl Butanoic Acids by Tripropylammonium Fluorochromate in Aqueous Acetic Acid Medium - Yogananth, A.; Asghar, Basim H.; Mansoor, S. Sheik (Asian Journal of Chemistry, 2017)
The kinetics of oxidation of 4-oxo-4-phenyl butanoic acid (4-oxo acid), p-methoxy (p-OCH3), p-ethoxy (p-OC2H5), p-methyl (p-CH3), p-chloro (p-Cl), p-bromo (p-Br) and p-acetyl (p-COCH3) 4-oxo acids by tripropylammonium fluorochromate (TriPAFC) in aqueous acetic acid medium in the presence of perchloric acid have been described. The reaction is first order with respect to 4-oxo acid, TriPAFC and perchloric acid. The order of reactivity among the studied 4-oxoacids is: p-OCH3 > p-OC2H5 > p-CH3 > p-H > p-Cl > p-Br > p-COCH3. The effect of changes on the electronic nature of the substrate reveals that there is a development of positive charge in the transition state. The activation parameters have been computed from Arrhenius and Eyring plots. Based on the kinetic results, a suitable mechanism has been proposed.